2010
DOI: 10.1186/1476-511x-9-134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kurozu concentrated liquid on adipocyte size in rats

Abstract: BackgroundKurozu concentrated liquid (KCL) is used as a health-promoting supplement for the treatment of disorders such as cancer, hyperlipidemia, and hypertension in Japan. We investigated the possible anti-obesity effects of KCL in rats.MethodsMale Sprague Dawley rats were fed American Institute of Nutrition 76 formula diet and were orally administrated KCL or acetic acid at a dose of 100 mg/kg body weight or deionized water for 4 weeks. Adipocyte size, DNA content in subcutaneous adipose tissue, lipid level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
2
17
1
1
Order By: Relevance
“…Differentiation was induced in 3T3-L1 cells in the presence of 10 % serum from these bloods. The numbers of cells (a) and lipid droplets (b) and the lipid area (c) were quantified as described in ''Materials and methods '' tissues significantly decreased and the number of small adipocytes in various tissues significantly increased in rats treated with Kurozu concentrated liquid (Tong et al 2010). However, in this study, we observed that Kibizu more strongly suppressed lipid accumulation in 3T3-L1 cells than Kurozu, suggesting that active components differ between these vinegars.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Differentiation was induced in 3T3-L1 cells in the presence of 10 % serum from these bloods. The numbers of cells (a) and lipid droplets (b) and the lipid area (c) were quantified as described in ''Materials and methods '' tissues significantly decreased and the number of small adipocytes in various tissues significantly increased in rats treated with Kurozu concentrated liquid (Tong et al 2010). However, in this study, we observed that Kibizu more strongly suppressed lipid accumulation in 3T3-L1 cells than Kurozu, suggesting that active components differ between these vinegars.…”
Section: Discussioncontrasting
confidence: 52%
“…We previously showed that the number of small adipocytes increased and that of large adipocytes decreased in adipocyte tissues in Kurozu-treated rats (Tong et al 2010). Here, we evaluated the effects of a novel vinegar made from sugar cane, Kibizu, on lipid accumulation in adipocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Fukuchi et al [46] indicated that citrus bioactive phenolics were reported to promote less body weight gain and white adipose tissue gain in mice after feeding of a HFD. Acetic acid is a major ingredient of vinegar, representing 6% of vinegar by volume, and it has also been shown to affect metabolic regulation and to have weight-reducing effects and alleviate hyperlipidemia [17,19,20,26,27]. Therefore, in this study, we determined whether acetic acid or bioactive compounds, components of vinegar, were had stronger anti-obesity effects.…”
Section: Discussionmentioning
confidence: 99%
“…It regulates appetite and energy metabolism by suppressing appetite and providing a feeling of satiety, and it is known that obesity increases leptin secretion [27,51]. In general, serum leptin concentration is proportional to body fat mass, and when excess energy accumulates, production is increased; thus, it is widely used as an indicator of obesity [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation